Physical properties of the photodamaged human skin dermis: Rougher collagen surface and stiffer/harder mechanical properties. Issue 8 (29th July 2018) - Shao, Yuan; Qin, Zhaoping; Alexander Wilks, James; Balimunkwe, Rebecca Mutesi; Fisher, Gary J.; Voorhees, John J.; Quan, Taihao
Abstract: Fragmentation of collagen fibrils and aberrant elastic material (solar elastosis) in the dermal extracellular matrix (ECM) is among the most prominent features of photodamaged human skin. These alterations impair the structural integrity and create a dermal microenvironment prone to skin disorders. The objective of this study was to determine the physical properties (surface roughness, stiffness and hardness) of the dermal ECM in photodamaged and subject‐matched sun‐protected human skin. Skin samples were sectioned and analysed by histology, atomic force microscopy and nanoindentation. Dermal ECM collagen fibrils were more disorganized (ie, rougher surface), and the dermal ECM was stiffer and harder, in photodamaged forearm, compared to sun‐protected underarm skin. Cleavage of collagen fibrils in sun‐protected underarm dermis by recombinant human matrix metalloproteinase‐1 resulted in rougher collagen fibril surface and reduced dermal stiffness and hardness. Degradation of elastotic material in photodamaged skin by treatment with purified neutrophil elastase reduced stiffness and hardness, without altering collagen fibril surface roughness. Additionally, expression of two members of the lysyl oxidase gene family, which insert cross‐links that stiffen and harden collagen fibrils, was elevated in photodamaged forearm dermis. These data elucidate the contributions of fragmented collagen fibrils, solar elastosis and elevated collagen cross‐linking to the physical properties of the dermal ECM in photodamaged human skin. This new knowledge extends current understanding of the impact of photodamage on the dermal ECM microenvironment.